Energy Efficiency in Developing Countries: A Systematic Review of Current Findings and Directions towards a Net Zero Economy - Mohamed, Erna Farina; Abdullah, Azlina; Jaaffar, Amar Hisham (International Journal of Energy Economics and Policy, 2024)
In an era marked by growing concerns about climate change and sustainable development, the interconnection between energy efficiency, economic growth, and environmental sustainability has emerged as a critical area of inquiry. This systematic literature review (SLR) examines a number of studies published between 2013 and 2023, concentrating on the multifaceted impact of energy efficiency on both economic growth and the environment. The primary objective of this review is to synthesize the existing literature to provide insights into the complex connections between energy efficiency and its impact both on the economy and the environment. In addition, this study investigates potential trade-offs and decoupling, particularly within the framework of developing nations. The PRISMA method was used in conducting the study which covered only journal articles published in Scopus and the Web of Science (WOS). As a result, 75 articles were reviewed - 23 articles for the growth impact, 37 articles for the environmental impact, and the remaining 15 articles, for both impacts and decoupling results. By critically analyzing research from the past decade, this review provides valuable insights for policymakers, researchers and practitioners working towards a sustainable and low-carbon economy.